Venture capital and innovation in Latin America - Luis Felipe Jiménez (CEPAL Review, 2008)
One of the drivers of economic growth is innovation, which raises productivity by creating new production methods, technologies, products and firms. This article examines an instrument that supports this process, venture capital, and highlights the need for a financing system covering each phase of innovation. It starts by illustrating Latin America’s innovation deficit. It then proceeds to a general analysis of the difficulties affecting the financing of innovation and the provision of venture capital to overcome these. It goes on to examine the form taken by these obstacles in the region and, considering the experience of Brazil and Chile, the methods used to deal with them. In relation to a number of the subjects addressed, the article discusses issues connected with major problems of financial system development.